Glioblastoma 2017
DOI: 10.15586/codon.glioblastoma.2017.ch10
|View full text |Cite
|
Sign up to set email alerts
|

PET for Therapy Response Assessment in Glioblastoma

Abstract: Glioblastoma (GB) is the most malignant and the most common type of glioma in adults, accounting for 60-70% of all malignant gliomas. Despite the current therapy, the clinical course of GB is usually rapid, with a mean survival time of approximately 1 year. For therapy response assessment in GB, magnetic resonance imaging (MRI) is the method of choice. In 2010, the Response Assessment in Neuro-Oncology (RANO) was introduced, including the tumor size (in 2D) as measured on T2-weighted and Fluid Attenuated Inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 118 publications
0
16
0
Order By: Relevance
“…This radiotracer (half-life of 109.7 min) is the most widely used for detecting the glucose uptake by tumor cells [86,87]. The main objective of using PET analysis in GBM cases is to differentiate tumor recurrence from radiation necrosis [61]. There is a linear relationship in PET signals between GBM cell number and 18 F-FDG uptake levels by these cells, that is significantly higher in small cell lung cancer with activity [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This radiotracer (half-life of 109.7 min) is the most widely used for detecting the glucose uptake by tumor cells [86,87]. The main objective of using PET analysis in GBM cases is to differentiate tumor recurrence from radiation necrosis [61]. There is a linear relationship in PET signals between GBM cell number and 18 F-FDG uptake levels by these cells, that is significantly higher in small cell lung cancer with activity [88].…”
Section: Discussionmentioning
confidence: 99%
“…Another important technique for therapeutic follow up analysis in glioma models is the PET that display functional and biological information, such as metastatic lesion and tumor level staging of III and IV [49,[58][59][60][61][62]. PET has high diagnostic, prognostic, and therapeutic evaluation value when integrating with CT or MRI informations [61,62] for drug metabolism and PET radiotracers as 18 F-2-fluoro-2-deoxy-D-glucose ( 18 F-FDG) which evaluates glucose metabolism. High-grade gliomas, such as GBM, are known to consume high glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce uptake in healthy brain, complete fasting for a minimum of 6 h before the scan is recommended, and patients should be kept blindfolded in a quiet room during the uptake phase, or scanning times should be delayed [23]. With applying these procedures, [ 18 F]FDG has shown acceptable sensitivity for the identification of anaplastic abnormalities in patients with low-grade glioma (LGG), high-grade glioma (HGG; Figure 1a [24]), CNS lymphoma, brain metastases, and meningioma [25][26][27]. Moreover, higher [ 18 F]FDG uptake has shown a positive correlation with higher histologic grade and worse prognosis [26,28], making [ 18 F]FDG PET a suitable tool for the prediction of progression-free survival (PFS) and overall survival (OS) [29].…”
Section: Diagnostic Imaging Of Abnormal Metabolic Processesmentioning
confidence: 99%
“…In addition, [ 18 F]FDG cannot distinguish between radiation-induced necrosis, changes in the tissue due to surgery, inflammation, or (remnant/recurrent) disease, making [ 18 F]FDG not valuable for follow-up studies of CNS tumor therapies [21,22]. (a) [24]. This research was originally published in Glioblastoma Table 1) [21,22,[31][32][33][34][35][36][37][38].…”
Section: Diagnostic Imaging Of Abnormal Metabolic Processesmentioning
confidence: 99%
“…However, localization and delineation of (primary) brain tumors is often difficult due to the high background glucose metabolism of normal brain parenchyma. Only coregistration of [ 18 F]FDG PET with MRI allows accurate assessment of glucose metabolism in specific areas of the tumor (5, 36, 39). Despite this phenomenon, it is worth mentioning that it has been demonstrated that delayed [ 18 F]FDG imaging (3–8 h after tracer injection) improves the distinction between tumor and normal gray matter because the washout of glucose is higher in normal brain tissue than in tumor tissue (39, 40).…”
Section: Pet Imaging In Glioblastomamentioning
confidence: 99%